Complete genome sequence and structural characterization of a novel iflavirus isolated from Opsiphanes invirae (Lepidoptera: Nymphalidae) - Silva, Leonardo A.; Ardisson-Araujo, Daniel M. P.; Tinoco, Ricardo S.; Fernandes, Odair A. [UNESP]; Melo, Fernando L.; Ribeiro, Bergmann M. (Elsevier B. V., 2015)
Opsiphanes invirae (Lepidopera: Nymphalidae) is a common pest of the African oil palm tree (Elaeis guineensis) in Brazil. Dead larvae were collected in canopy of oil palm trees cultivated in the amazon region (Para State) and analyzed for viral infection. Electron microscopy of caterpillar extracts showed an icosahedral picorna-like virus particle with 30nm in diameter. Total RNA extracted from partially purified virus particles was sequenced. A contig of 10,083 nucleotides (nt) was identified and showed to encode one single predicted polyprotein with 3185 amino acid residues. Phylogenetic analysis showed that the new virus was closely related to another lepidopteran infective virus Spodoptera exigua iflavirus 1(SeIV-1), with 35% amino acid pairwise identity. The novel virus fulfils all ICTV requirements for a new iflavirus species and was named Opsiphanes invirae Iflavirus 1 (OilV-1).
Keywords: Biological control; Genome sequencing; Iflavirus; Opsiphanes invirae; Picorna-like virus